Progress in the CO2 Capture Technologies for Fluid Catalytic Cracking (FCC) Units—A Review - Güleç, Fatih; Meredith, Will; Snape, Colin E. (Frontiers in Energy Research, 2020)
Heavy industries including cement, iron and steel, oil refining, and petrochemicals are collectively responsible for about 22 % of global CO2 emissions. Among these industries, oil refineries account for 4-6 %, of which typically 25-35 % arise from the regenerators in Fluid Catalytic Cracking (FCC) units. This article reviews the progress in applying CO2 capture technologies to FCC units. Post combustion and Oxyfuel combustion have been investigated to mitigate CO2 emissions in FCC and, more recently, Chemical Looping Combustion (CLC) has received attention. Post combustion can readily be deployed to the flue gas in FCC units and Oxyfuel combustion, which requires air separation, has been investigated in a pilot-scale unit by Petrobras (Brazil). However, in comparison, CLC offers considerably lower energy penalties. The applicability of CLC for FCC has also been experimentally investigated using acceptable lab-scale modifications up to now. As a result, the studies demonstrated highly promising CO2 capture capacities for FCC with the application of Post combustion (85-90 %), Oxyfuel combustion (90-100 %) and CLC (90-96 %). Therefore, the method having lowest energy penalty and CO2 avoided cost is highly important for the next generation of FCC units to optimise CO2 capture. The energy penalty was calculated as 3.1-4.2 GJ/t CO2 with an avoiding cost of 75-110 €/t CO2 for the application of Post combustion to FCC. However, the application of Oxyfuel combustion provided lower energy penalty of 1.8-2.5 GJ/t CO2, and lower CO2 avoided cost of 55-85 €/t CO2. More recently, lab-scale experiments demonstrated that the application of CLC to FCC demonstrate significant progress and relatively low energy penalty of 0.2 GJ/t CO2.